2011
DOI: 10.1053/j.gastro.2011.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Ductal Plate Cells Give Rise to Cholangiocytes, Periportal Hepatocytes, and Adult Liver Progenitor Cells

Abstract: Background & Aims Embryonic biliary precursor cells form a periportal sheet called the ductal plate, which is progressively remodeled to generate intrahepatic bile ducts. A limited number of ductal plate cells participate in duct formation; those not involved in duct development are believed to involute by apoptosis. Moreover, cells that express the SRY-related HMG box transcription factor 9 (SOX9), which include the embryonic ductal plate cells, were proposed to continuously supply the liver with hepatic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
240
2
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(268 citation statements)
references
References 23 publications
22
240
2
4
Order By: Relevance
“…We have confirmed this with the use of a Sox9-CreER mouse strain (19). It has been shown that Sox9 is up-regulated in adult hepatocytes by tamoxifen, making it difficult to label Sox9 + cells in adulthood (19).…”
Section: Ad-pnm Gives Long-term Diabetes Relief With the Formation Ofsupporting
confidence: 60%
See 3 more Smart Citations
“…We have confirmed this with the use of a Sox9-CreER mouse strain (19). It has been shown that Sox9 is up-regulated in adult hepatocytes by tamoxifen, making it difficult to label Sox9 + cells in adulthood (19).…”
Section: Ad-pnm Gives Long-term Diabetes Relief With the Formation Ofsupporting
confidence: 60%
“…Moreover the experiments with the Sox9-CreER; mTmG mice show that they arise from cells labeled for Sox9 expression at the ductal plate stage of development. These are probably small bile ducts (22,23) but the cells of origin might also be hepatoblastlike progenitor cells, thought to be in the periportal region associated with small bile ducts (26,27) or perhaps they derive from the peribiliary glands, which are associated with larger bile ducts and are reported to contain cells expressing markers characteristic of embryonic endoderm (18,19,(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ALGS patients are born with an intact biliary system (51), but the ratio of bile ducts to liver tissue quickly declines with age after birth, which leads to cholestasis and presentation with ALGS liver disease (7,52,53). The proximal branches of the biliary tree are formed in embryonic liver from a single layer of bipotent precursor cells that surround the portal vein (the ductal plate), which are progressively remodeled to generate intrahepatic bile ducts (54), and this requires an interaction with surrounding mesodermal tissues (55). However, the liver enlarges 3-fold during the postnatal period, which is when ALGS liver abnormalities first appear.…”
Section: Discussionmentioning
confidence: 99%